Enhancing phosphorus removal of photogranules by incorporating polyphosphate accumulating organisms. (15th May 2023) - Trebuch, Lukas M.; Sohier, Jasper; Altenburg, Sido; Oyserman, Ben O.; Pronk, Mario; Janssen, Marcel; Vet, Louise E.M.; Wijffels, René H.; Fernandes, Tânia V.
Highlights: Successful enrichment of photogranules with PAOs (termed PG+) after 2–3 weeks. Up to 6x higher phosphorus recovery with PG+ compared to native photogranules. 2–3x higher biomass productivity of PG+ compared to aerobic granular sludge. No adverse effect of 12-h anaerobic phase on reactor function or microbial community. Abstract: Photogranules are a novel wastewater treatment technology that can utilize the sun's energy to treat water with lower energy input and have great potential for nutrient recovery applications. They have been proven to efficiently remove nitrogen and carbon but show lower conversion rates for phosphorus compared to established treatment systems, such as aerobic granular sludge. In this study, we successfully introduced polyphosphate accumulating organisms (PAOs) to an established photogranular culture. We operated photobioreactors in sequencing batch mode with six cycles per day and alternating anaerobic (dark) and aerobic (light) phases. We were able to increase phosphorus removal/recovery by 6 times from 5.4 to 30 mg/L/d while maintaining similar nitrogen and carbon removal compared to photogranules without PAOs. To maintain PAOs activity, alternating anaerobic feast and aerobic famine conditions were required. In future applications, where aerobic conditions are dependent on in-situ oxygenation via photosynthesis, the process will rely on sunlight availability. Therefore, we investigated the feasibility of the process under diurnal cycles with a 12-h anaerobic phase during nighttime and six short cycles during the 12 h daytime. The 12-h anaerobic phase had no adverse effect on the PAOs and phototrophs. Due to the extension of one anaerobic phase to 12 h the six aerobic phases were shortened by 47% and consequently decreased the light hours per day. This resulted in a decrease of phototrophs, which reduced nitrogen removal and biomass productivity up to 30%. Finally, we discuss and suggest strategies to apply PAO-enriched photogranules at large-scale. Graphical abstract: Image, graphical abstract